211k views
3 votes
Use the quadratic formula to solve for the roots of the following equation.
x 2 – 4x + 13 = 0

User Martriay
by
4.9k points

2 Answers

2 votes

x = [ -(-4) +/- sqrt ( (-4)^2 - 4*1*13) ] / 2

x = (4 + sqrt -36) / 2 , (4 - sqrt -36) / 2

x = (4 + 6i) / 2 , (4 - 6i) 2

x = 2 + 3i , 2 - 3i Answer

User Kqtr
by
5.4k points
5 votes
  • Quadratic Formula:
    x=(-b\pm √(b^2-4ac))/(2a) , with a = x^2 coefficient, b = x coefficient, and c = constant

With our equation, plug in the values:


x=(4\pm √((-4)^2-4*1*13))/(2*1)

Next, solve the exponent and multiplications:


x=(4\pm √(16-52))/(2)

Next, solve the subtraction:


x=(4\pm √(-36))/(2)

Next, factor out i (i = √-1):


x=(4\pm √(36)i)/(2)

Next, solve the square root:


x=(4\pm 6i)/(2)

Lastly, divide and your answer is:


x=2\pm 3i

User Andrzej Zabost
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.